Ambiguities of social Europe: Political agenda setting among trade unionists from Central and Eastern Europe and Western Europe - Martin Seeliger (Max Planck Institute for the Study of Societies, 2017)
The article analyzes the integration of Central and Eastern European (CEE) trade unions in European policy-making. With reference to transnational cooperation in two fields of European-level decision making (issues concerning freedom of services and a European minimum wage), it investigates the extent to which trade unions from the CEE countries are participating in the development of policy positions among European-level trade union organizations. On this basis, the article highlights three things: (1) the instrumental meaning of "Social Europe," (2) the necessity of a mid-way position between optimistic and pessimistic viewpoints on East-West trade union cooperation, and (3) the meaning of social skill among European-level trade union actors. – – Der Artikel analysiert die Einbindung zentral- und osteuropäischer Gewerkschafter in die europäische Entscheidungsebene. Unter Bezug auf die transnationale Zusammenarbeit in zwei Politikfeldern (Dienstleistungsfreiheit sowie die Diskussion um den europäischen Mindestlohn) zeigt der Text, inwiefern zentral- und osteuropäische Vertreter dort auf Augenhöhe an der Entwicklung gemeinsamer Positionen beteiligt werden. Auf dieser Grundlage arbeitet der Artikel drei Aspekte heraus: den instrumentellen Charakter des Begriffs eines "sozialen Europas", die Notwendigkeit einer zwischen Euro-Optimisten und Euro-Pessimisten vermittelnden Position sowie die Bedeutung von "social skill" für die praktische Auseinandersetzung von Akteuren in der europäischen Gewerkschaftspolitik.
hdl:11858/00-001M-0000-002C-603A-8
Keywords: 300; Social Europe; trade unionism; eastern enlargement; labor transnationalism; European integration; Soziales Europa; Gewerkschaften; Osterweiterung; Internationalismus; europäische Integration